Ectrodactyly, ectodermal dysplasia, and cleft lip/palate syndrome: A case report of "Incomplete syndrome" - P K Shivaprakash; Hrishikesh V Joshi; Hina Noorani; Venugopal Reddy (Wolters Kluwer Medknow Publications, 2012)
Ectrodactyly, ectodermal dysplasia, and cleft lip/palate (EEC) is a rare syndrome having ectrodactyly, ectodermal dysplasia, and cleft lip/palate. So far, very few cases have been reported in literature. However, we report a case of incomplete EEC syndrome having ectrodactyly and cleft lip and palate with absence of signs of ectodermal dysplasia with no other systemic anomalies. Other feature noted is the syndactyly of toes which is reported rarely in this syndrome. A multidisciplinary approach for treatment is needed which is co-ordinated by pedodontist or pediatrician.